# Solve the equation and calculate the value of x

$\dfrac{{4x}}{{x - 2}} - \dfrac{{3x}}{{x - 1}} = 7\dfrac{1}{2}$

$

A. {\text{ }}x = 0,\dfrac{{10}}{{13}} \\

B. {\text{ }}x = 3,\dfrac{{10}}{{13}} \\

C. {\text{ }}x = 3, - \dfrac{1}{{13}} \\

D. {\text{ None of these}} \\

$

Last updated date: 13th Mar 2023

•

Total views: 304.8k

•

Views today: 5.85k

Answer

Verified

304.8k+ views

Hint: In this question first simplify the L.H.S part of the equation and later on apply the property of cross multiplication, so use these concepts to reach the solution of the question.

Complete step-by-step answer:

Given equation is

$\dfrac{{4x}}{{x - 2}} - \dfrac{{3x}}{{x - 1}} = 7\dfrac{1}{2}$

As we know $7\dfrac{1}{2}$is also written as $\dfrac{{\left( {7 \times 2} \right) + 1}}{2} = \dfrac{{15}}{2}$, substitute this value in above equation we have,

$\dfrac{{4x}}{{x - 2}} - \dfrac{{3x}}{{x - 1}} = \dfrac{{15}}{2}$

Now take L.C.M of the above equation we have,

$\dfrac{{4x\left( {x - 1} \right) - 3x\left( {x - 2} \right)}}{{\left( {x - 2} \right)\left( {x - 1} \right)}} = \dfrac{{15}}{2}$

Now simplify the numerator and denominator of the L.H.S we have

$ \Rightarrow \dfrac{{4{x^2} - 4x - 3{x^2} + 6x}}{{{x^2} - x - 2x + 2}} = \dfrac{{15}}{2}$

$ \Rightarrow \dfrac{{{x^2} + 2x}}{{{x^2} - 3x + 2}} = \dfrac{{15}}{2}$

Now apply cross multiply we have

$ \Rightarrow 2\left( {{x^2} + 2x} \right) = 15\left( {{x^2} - 3x + 2} \right)$

Now simplify the above equation we have,

$

\Rightarrow 2{x^2} + 4x = 15{x^2} - 45x + 30 \\

\Rightarrow 15{x^2} - 2{x^2} - 45x - 4x + 30 = 0 \\

\Rightarrow 13{x^2} - 49x + 30 = 0 \\

$

Now divide by 13 in the above equation we have,

$ \Rightarrow {x^2} - \dfrac{{49}}{{13}}x + \dfrac{{30}}{{13}} = 0$

Now factorize the above equation we have,

$ \Rightarrow {x^2} - 3x - \dfrac{{10}}{{13}}x + \dfrac{{30}}{{13}} = 0$

$

\Rightarrow x\left( {x - 3} \right) - \dfrac{{10}}{{13}}\left( {x - 3} \right) = 0 \\

\Rightarrow \left( {x - 3} \right)\left( {x - \dfrac{{10}}{{13}}} \right) = 0 \\

\Rightarrow \left( {x - 3} \right) = 0,{\text{ }}\left( {x - \dfrac{{10}}{{13}}} \right) = 0 \\

\Rightarrow x = 3,{\text{ }}\dfrac{{10}}{{13}} \\

$

So, this is the required solution of the question.

Hence, option (b) is correct.

Note: In such types of questions simplification is the key, so simplify the above equation as above doing simplification don’t make unnecessary mistakes it will lead us to wrong answer so be careful while doing addition, subtraction, division and multiplication then apply cross multiply and again simplify then factorize the equation we will get the required solution of the x.

Complete step-by-step answer:

Given equation is

$\dfrac{{4x}}{{x - 2}} - \dfrac{{3x}}{{x - 1}} = 7\dfrac{1}{2}$

As we know $7\dfrac{1}{2}$is also written as $\dfrac{{\left( {7 \times 2} \right) + 1}}{2} = \dfrac{{15}}{2}$, substitute this value in above equation we have,

$\dfrac{{4x}}{{x - 2}} - \dfrac{{3x}}{{x - 1}} = \dfrac{{15}}{2}$

Now take L.C.M of the above equation we have,

$\dfrac{{4x\left( {x - 1} \right) - 3x\left( {x - 2} \right)}}{{\left( {x - 2} \right)\left( {x - 1} \right)}} = \dfrac{{15}}{2}$

Now simplify the numerator and denominator of the L.H.S we have

$ \Rightarrow \dfrac{{4{x^2} - 4x - 3{x^2} + 6x}}{{{x^2} - x - 2x + 2}} = \dfrac{{15}}{2}$

$ \Rightarrow \dfrac{{{x^2} + 2x}}{{{x^2} - 3x + 2}} = \dfrac{{15}}{2}$

Now apply cross multiply we have

$ \Rightarrow 2\left( {{x^2} + 2x} \right) = 15\left( {{x^2} - 3x + 2} \right)$

Now simplify the above equation we have,

$

\Rightarrow 2{x^2} + 4x = 15{x^2} - 45x + 30 \\

\Rightarrow 15{x^2} - 2{x^2} - 45x - 4x + 30 = 0 \\

\Rightarrow 13{x^2} - 49x + 30 = 0 \\

$

Now divide by 13 in the above equation we have,

$ \Rightarrow {x^2} - \dfrac{{49}}{{13}}x + \dfrac{{30}}{{13}} = 0$

Now factorize the above equation we have,

$ \Rightarrow {x^2} - 3x - \dfrac{{10}}{{13}}x + \dfrac{{30}}{{13}} = 0$

$

\Rightarrow x\left( {x - 3} \right) - \dfrac{{10}}{{13}}\left( {x - 3} \right) = 0 \\

\Rightarrow \left( {x - 3} \right)\left( {x - \dfrac{{10}}{{13}}} \right) = 0 \\

\Rightarrow \left( {x - 3} \right) = 0,{\text{ }}\left( {x - \dfrac{{10}}{{13}}} \right) = 0 \\

\Rightarrow x = 3,{\text{ }}\dfrac{{10}}{{13}} \\

$

So, this is the required solution of the question.

Hence, option (b) is correct.

Note: In such types of questions simplification is the key, so simplify the above equation as above doing simplification don’t make unnecessary mistakes it will lead us to wrong answer so be careful while doing addition, subtraction, division and multiplication then apply cross multiply and again simplify then factorize the equation we will get the required solution of the x.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE